Influence of Sex on Gestational Complications, Fetal-to-Neonatal Transition, and Postnatal Adaptation - Sheila Lorente-Pozo; Anna Parra-Llorca; Begoña Torres; Isabel Torres-Cuevas; Antonio Nuñez-Ramiro; Antonio Nuñez-Ramiro; María Cernada; María Cernada; Ana García-Robles; Maximo Vento; Maximo Vento (Frontiers Media S.A., 2018)
Fetal sex is associated with striking differences during in utero development, fetal-to-neonatal transition, and postnatal morbidity and mortality. Male sex fetuses are apparently protected while in utero resulting in a higher secondary sex rate for males than for females. However, during fetal-to-neonatal transition and thereafter in the newborn period, female exhibits a greater degree of maturation that translates into a better capacity to stabilize, less incidence of prematurity and prematurity-associated morbidities, and better long-term outcomes. The present review addresses the influence of sex during gestation and postnatal adaptation that includes the establishment of an adult-type circulation, the initiation of breathing, endurance when confronted with perinatal hypoxia ischemia, and a gender-related different response to drugs. The intrinsic mechanisms explaining these differences in the perinatal period remain elusive and further experimental and clinical research are therefore stringently needed if an individual oriented therapy is to be developed.